2015
DOI: 10.1162/jocn_a_00720
|View full text |Cite
|
Sign up to set email alerts
|

Size Precedes View: Developmental Emergence of Invariant Object Representations in Lateral Occipital Complex

Abstract: Visual motion perception is fundamental to many aspects of visual perception. Visual motion perception has long been associated with the dorsal (parietal) pathway and the involvement of the ventral 'form' (temporal) visual pathway has not been considered critical for normal motion perception. Here, we evaluated this view by examining whether circumscribed damage to ventral visual cortex impaired motion perception. The perception of motion in basic, non-form tasks (motion coherence and motion detection) and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 178 publications
5
26
0
Order By: Relevance
“…Planned comparisons revealed that all change types were responded to more slowly than the no-change controls (all P values ≤ .001, paired samples t-tests). When the change trials were compared against each other, it was found that Size changes were responded to more quickly than Object changes [t(22) = 5.86, P < .001], consistent with the idea that size information is processed very early in the processing stream, and, therefore, can be accessed for behaviour more quickly than laterprocessed object information (Larsen & Bundesen, 1978;Larsen, Bundesen, Kyllingsbaek, Paulson, & Law, 2000;Nishimura et al, 2015). More critically, it was found that Combination changes were responded to more slowly than Size changes [t(22) = 2.39, P = .026], but more quickly than Object changes [t(22) = 4.74, P < .001].…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Planned comparisons revealed that all change types were responded to more slowly than the no-change controls (all P values ≤ .001, paired samples t-tests). When the change trials were compared against each other, it was found that Size changes were responded to more quickly than Object changes [t(22) = 5.86, P < .001], consistent with the idea that size information is processed very early in the processing stream, and, therefore, can be accessed for behaviour more quickly than laterprocessed object information (Larsen & Bundesen, 1978;Larsen, Bundesen, Kyllingsbaek, Paulson, & Law, 2000;Nishimura et al, 2015). More critically, it was found that Combination changes were responded to more slowly than Size changes [t(22) = 2.39, P = .026], but more quickly than Object changes [t(22) = 4.74, P < .001].…”
Section: Resultssupporting
confidence: 55%
“…For example, object-level representations are housed later in the processing stream than representations of basic visual features like size (Grill-Spector et al, 1999;Nishimura, Scherf, Zachariou, Tarr, & Behrmann, 2015). Nonetheless, integration can occur between distantly held representations.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the fusiform gyrus, however, the LOC is thought to reach adult-like maturity by 5–8 years and does not show age-related changes in size or location beyond this age (Grill-Spector, Golarai, & Gabrieli, 2008; Golarai et al, 2007; Scherf et al, 2007). Although a recent study finds more fine-grained object recognition (e.g., size and view invariance) takes longer to develop in LOC (Nishimura, Scherf, Zachariou, Tarr, & Behrmann, 2015), this study did not require this level of object recognition.…”
Section: Discussionmentioning
confidence: 81%
“…The emergence of tolerance to different transformations has been shown to follow different developmental trajectories. A recent study on the neural basis of invariance has corroborated this finding, showing that size invariance develops earlier than view invariance (Nishimura et al, 2015).…”
Section: Introductionmentioning
confidence: 75%